PROFESI DOSEN SEBAGAI SUMBER DAYA MANUSIA DI PERGURUAN TINGGI ISLAM - Samsuni, Samsuni (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2023)
Human resource management in the lecturer profession is an important field of science to study considering the very important role of lecturers in the education system in higher education as stated in article 1 number 14 of 2005 concerning teachers and lecturers. Lecturers have a very important role in the education system at Islamic universities, not only conveying knowledge, but also as scientists and pioneers in serving society as well as transforming, developing and disseminating knowledge and shaping the character of the nation through applicable values and norms. . Apart from that, lecturers are professional educators and scientists who have the main task of transforming, developing and disseminating science, technology and art through education, research and community service.